Feminist theory reader : local and global perspectives - McCann, Carole R. (Carole Ruth), 1955-; Kim, Seung-Kyung, 1954-
The third edition of the Feminist Theory Reader anthologizes the important classical and contemporary works of feminist theory within a multiracial transnational framework. This edition includes 16 new essays; the editors have organized the readings into four sections, which challenge the prevailing representation of feminist movements as waves.